2019
DOI: 10.1016/j.scitotenv.2019.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Background levels of dioxin-like polychlorinated biphenyls (dlPCBs), polychlorinated, polybrominated and mixed halogenated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs, PBDD/Fs & PXDD/Fs) in sera of pregnant women in Accra, Ghana

Abstract: A (2019)Background levels of dioxinlike polychlorinated biphenyls (dlPCBs), polychlorinated, polybrominated and mixed halogenated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs, PBDD/Fs & PXDD/Fs) in sera of pregnant women in Accra, Ghana. Science of The Total Environment, 673. pp. 631-642.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 66 publications
0
6
1
Order By: Relevance
“…The total TEQs of PCDDs, PCDFs, and PCDD/Fs in maternal serum between this study and other studies globally are shown in Table 5. Mean ∑TEQ-PCDDs, ∑TEQ-PCDFs, and ∑TEQ-PCDD/Fs in the present study were higher than most background concentrations reported in the serum of pregnant women in other locations of the world (Baba et al, 2018;Bao et al, 2020;Boda et al, 2018;Bruce-Vanderpuije et al, 2019;Rodríguez Dozal S et al, 2011;Todaka et al, 2010;Yu DZ et al, 2019). ∑TEQ-PCDD/Fs in maternal serum were also compared with the biomonitoring equivalent (BE) for risk assessment.…”
Section: Discussioncontrasting
confidence: 44%
“…The total TEQs of PCDDs, PCDFs, and PCDD/Fs in maternal serum between this study and other studies globally are shown in Table 5. Mean ∑TEQ-PCDDs, ∑TEQ-PCDFs, and ∑TEQ-PCDD/Fs in the present study were higher than most background concentrations reported in the serum of pregnant women in other locations of the world (Baba et al, 2018;Bao et al, 2020;Boda et al, 2018;Bruce-Vanderpuije et al, 2019;Rodríguez Dozal S et al, 2011;Todaka et al, 2010;Yu DZ et al, 2019). ∑TEQ-PCDD/Fs in maternal serum were also compared with the biomonitoring equivalent (BE) for risk assessment.…”
Section: Discussioncontrasting
confidence: 44%
“…There are many biomonitoring studies of dioxins, such as in human serum [36], mother serum [37], cord blood [38,39], and so on, but only a few studies focused on umbilical cord serum. Wang et al reported the mean TEQ of 13.56 pg·g −1 lipid in cord serum of pregnant women in Taiwan [12].…”
Section: Resultsmentioning
confidence: 99%
“…Stress Ghana [126] Physical injury Brazil, Ghana, Nigeria, India [89,90,128] Excessive noise Ghana, China [130,131] Pregnancy-related issues China, Ghana [132][133][134][135][136] DNA damage China, Nigeria [137][138][139][140] Skin problems India, Brazil, Nigeria [89,90,127,129] Respiratory problems Ghana, India, Nigeria, China [89,90,113,141] Hearing problems Ghana, China, Nigeria, India [130,[142][143][144][145]…”
Section: Health Impact Country Referencementioning
confidence: 99%